Knowledge of osteoporosis and calcium and its association with dietary calcium intake among students in UTAR, Kampar - Tan, Hui Ning (2022)
Adequate calcium intake is important to achieve peak bone mass and prevent osteoporosis risks. Meanwhile, most Malaysians had a low calcium intake, below the recommended 1000 mg/day. Studies regarding the association between knowledge and calcium intake among university students are insufficient. Thus, this research aimed to assess the level of osteoporosis knowledge, calcium knowledge, and dietary calcium intake among students in Universiti Tunku Abdul Rahman (UTAR), Kampar as well as to determine the association between the three variables. A cross-sectional survey was conducted online among UTAR Kampar students between 19 to 30 years old from February 2022 to July 2022. A total of 165 respondents were recruited and completed the survey comprised of sociodemographic, osteoporosis knowledge, calcium knowledge, and food frequency questionnaires. One-way ANOVA and Independent t-test were used to examine the discrepancy in calcium intake among different knowledge levels. Pearson’s correlation was to determine the association between osteoporosis knowledge, calcium knowledge and dietary calcium intake. This study found that majority of respondents had moderate osteoporosis knowledge (63.6%) and good calcium knowledge (53.9%). Most students knew consumption of calcium-rich food can prevent osteoporosis (81.8%), but were unaware of the recommended calcium intake for their age (50.9%). Generally, females had higher knowledge with a significant difference (p<0.05) observed for osteoporosis knowledge, but not calcium knowledge. Besides, the dietary calcium intake of UTAR students was low with an average calcium consumption of 369.5±83.54 mg/day. Male students had a higher intake but no significant difference was reported. Calcium intake was significantly different between levels of osteoporosis knowledge and calcium knowledge (p<0.001). There were moderately positive associations reported between osteoporosis knowledge, calcium knowledge and dietary calcium intake (p<0.001). Overall, the students had decent osteoporosis and calcium knowledge levels, but their calcium intake remained low. Hence, future educational intervention is needed to enhance students’ attitude and calcium intake for effective osteoporosis prevention.